ANALISIS PEMENUHAN HAK EKONOMI, SOSIAL, DAN BUDAYA PEKERJA MIGRAN ASAL KOTA KUPANG DALAM PERSPEKTIF HAK ASASI MANUSIA TAHUN 2025 - Mersiana Wanda Tuti Issu; Fadil Mas’ud; Stefynia Adriana Lengo; Sepete Adrian Mangngi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the economic, social, and cultural rights of migrant workers from a human rights perspective in 2025. Kupang City, located in East Nusa Tenggara Province, is one of the regions with a relatively high rate of overseas labor migration, particularly to Malaysia and the Middle East. Limited local employment opportunities, inadequate social security, and a strong migrant culture in the city are the key drivers of this migration. This research employs a qualitative descriptive approach using a literature review method. Data were collected by reviewing and evaluating relevant papers and literature sources. The findings indicate that the economic rights of migrant workers remain insufficiently protected due to inadequate employment contracts and weak oversight by labor agencies. In social and cultural aspects, many migrant workers experience social disruption, discrimination, and loss of cultural identity. Although the local government provides pre-departure training and counseling, its coverage remains limited and its effectiveness needs improvement. The study recommends strengthening human rights–based protection policies, establishing city-level service centers for migrant workers, and enhancing public understanding of legal frameworks.